Pengaruh Penerapan Model Pembelajaran Auditory Intellectually Repetition (AIR) terhadap Hasil Belajar Matematika Siswa di Kelas VII SMP Negeri 3 Muara Batang Gadis - Intan Sari; Adek Nilasari Harahap; Nurdalilah (Journal Education Innovation (JEI), 2025)
This study aims to determine the effect of Auditory Intellectually Repetition (AIR) learning model on mathematics learning outcomes of seventh grade students of SMP Negeri 3 Muara Batang Gadis. The method used was quantitative pseudo experiment with Nonequivalent Control Group Design. The sample consisted of two classes, namely experimental class taught using AIR model and control class using conventional method. The instrument used was a math learning outcome test in the form of multiple choice and description, which was given before and after treatment. Data analysis was conducted through normality test, homogeneity, t-test, and N-Gain calculation. The results showed a significant increase in the average post-test score in the experimental class. The N-Gain value of the experimental class reached 0.627 (medium-high category), while the control class was only 0.365 (medium category). The t-test showed a significance value of p = 0.000 (p < 0.05), which means there is a significant difference in learning outcomes between the two groups. Thus, the AIR learning model is proven effective in improving students' mathematics learning outcomes and is recommended to be applied in the learning process at school.